Forty-four-year longitudinal study of stroke incidence and risk factors - the Prospective Population Study of Women in Gothenburg - Ann Blomstrand; Christian Blomstrand; Magnus Hakeberg; Valter Sundh; Lauren Lissner; Cecilia Björkelund (Taylor & Francis Group, 2022)
Objective To assess stroke incidence over 44 years and association with risk factors. To study total stroke incidence at 60-82 years of age and risk factors.Design Prospective population study.Setting Gothenburg, Sweden, with ∼450,000 inhabitants.Subjects A representative sample of a general population of women (1462 in total) in 5 age strata aged 38-60 years in 1968-1969 (the Population Study of Women in Gothenburg, PSWG) were followed up to the ages of 82-104 years in 2012. Further, analysis was also performed for the age interval 60-82 years.Main outcome measures Incidence of total stroke (TS), ischaemic (IS), haemorrhagic (HS), non-specified (NS) and fatal (FS) strokes and association with baseline classic risk factors (such as hypertension, atrial fibrillation, low physical activity, diabetes, high waist-hip-ratio, hyperlipidaemia, smoking), low education, mental stress, pre-eclampsia and oral health as expressed by loss of teeth and bone score. Blood pressure in levels 1-3 according to modern guidelines. Associations with atrial fibrillation, diabetes and myocardial infarction shown in survival analyses. The five cohorts contributed to risk time data concerning associations with TS in the 60-82 age interval from the examination performed when they were 60.Results Three hundred and thirty-seven (23%) women had a first-ever stroke, 64 (19%) fatal. TS was associated with physical inactivity, high triglycerides and low education in multivariable analysis. The main sub-type IS was associated with systolic blood pressure, physical inactivity and low education. Pre-eclampsia showed association with IS only in the univariable analysis. FS was associated with systolic blood pressure and smoking. During 60-82 years of age, having <20 teeth (HR 1.74, CI 1.25-2.42), diabetes (HR 2.28 CI 1.09-4.76), WHR (HR 1.29 per 0.1 units CI 1.01-1.63), systolic blood pressure (HR 1.11 per 10 units CI 1.04-1.18) and smoking (HR 1.57, CI 1.14-2.16), were associated with TS in the combined five cohorts.Conclusions Several classic risk factors showed independent associations with stroke. Vulnerability factors as low education and oral health, reflected by loss of teeth, also showed association with stroke. All these factors are possible to target in primary care preventive interventions.Key PointsStroke is a common disease and the risk of stroke is a key issue demanding preventive strategies in primary health care. The present prospective population study of women showsOut of 1460 women, almost a quarter got a stroke. The stroke incidence 60-82 years of age was rather stable between the first four age cohorts but somewhat lower in the latest cohort, born 1930.Hypertension, low physical activity, low education and high triglyceride levels but not cholesterol were associated with stroke in women.Low education and loss of teeth are vulnerability factors that should need particular attention.